Antimicrobial Usage and Detection of Multidrug-Resistant Staphylococcus aureus: Methicillin- and Tetracycline-Resistant Strains in Raw Milk of Lactating Dairy Cattle - Lubna; Tahir Hussain; Ashwag Shami; Naseem Rafiq; Shehryar Khan; Muhammad Kabir; Naimat Ullah Khan; Irfan Khattak; Mustafa Kamal; Tahir Usman (MDPI AG, 2023)
Staphylococcus aureus is a prominent cause of food-borne diseases worldwide. Enterotoxigenic strains of this bacteria are frequently found in raw milk, and some of these strains are resistant to antimicrobials, posing a risk to consumers. The main objectives of this study were to determine the antimicrobial resistance pattern of S. aureus in raw milk and to detect the presence of mecA and tetK genes in it. A total of 150 milk samples were obtained aseptically from lactating cattle, including Holstein Friesian, Achai, and Jersey breeds, maintained at different dairy farms. The milk samples were checked for the presence of S. aureus, and it was detected in 55 (37%) of them. The presence of S. aureus was verified by culturing on selective media, gram staining, and performing coagulase and catalase tests. Further confirmation was performed through PCR with a species-specific thermonuclease (nuc) gene. Antimicrobial susceptibility testing of the confirmed S. aureus was then determined by using the Kirby-Bauer disc diffusion technique. Out of the 55 confirmed S. aureus isolates, 11 were determined to be multidrug-resistant (MDR). The highest resistance was found to penicillin (100%) and oxacillin (100%), followed by tetracycline (72.72%), amikacin (27.27%), sulfamethoxazole/trimethoprim (18.18%), tobramycin (18.18%), and gentamycin (9.09%). Amoxicillin and ciprofloxacin were found to be susceptible (100%). Out of 11 MDR S. aureus isolates, the methicillin resistance gene (mecA) was detected in 9 isolates, while the tetracycline resistance gene (tetK) was found in 7 isolates. The presence of these methicillin- and tetracycline-resistant strains in raw milk poses a major risk to public health, as they can cause food poisoning outbreaks that can spread rapidly through populations. Our study concludes that out of nine empirically used antibiotics, amoxicillin, ciprofloxacin, and gentamicin were highly effective against S. aureus compared to penicillin, oxacillin, and tetracycline.